Studi Pemanfaatan Limbah Material Polypropilene (PP) untuk Pembuatan Produk Cone Benang dengan Penambah Material Kalsium Karbonat - Adhi Setya Hutama (Universitas Katolik Parahyangan, 2022)
Based on data from SIPSN (Sistem Informasi Pengolahan Sampah Nasional) Ministry of Environment and Forestry, Indonesia's waste stockpile in 2020 reached 33 million tons, and 17.12% of it was plastic waste. The government has several alternative solutions in waste management, such as the creation of a waste bank, compost house, maximizing the 3R (reduce, reuse, and recycle) program, and applied plastic waste for renewable energy. Research on the use of PP plastic waste for the manufacture of recycled yarn cones is also included in the use of the 3R program which is being discussed by the government. The aim of this research is to obtain the mechanical characteristics (flexural strength) and mass weight between the cones made from recycled PP and pure PP. Based on the observations that have been made, the cone product with PP material has a compressive strength characteristic of 0.4 – 0.8 kg/mm2 and a weight of 10.5 – 11.5 grams. The study of the use of PP plastic waste to be used as a cone product begins with preliminary research related to optimizing product manufacturing parameters on injection machines. The next step process is making cone products with added calcium material. After the product has been printed, the next step is flexural testing and measurement of the mass of the product. Based on the test results, the product of pure PP cone material with 5% and 10% calcium carbonate added, and recycled PP material with 15% calcium carbonate addition is the result that meets the mass standard (10.5 g to 11.5 g) and flexural strength. (0.4 kg/mm2 to 0.8 kg/mm2). Because the focus of research is on the use of plastic waste, so the ideal cone product is recycled PP material with the addition of 15% calcium carbonate.